Linguistic and Contextual Analysis of Fasting in Surah al-Baqarah: A Jewish-Christian Heritage in 7th Century Arabia - Ismail, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research examines the Islamic obligation of fasting during the month of Ramadan as outlined in the Quran (Q 2:183-5). The author argues that many Islamic scholars have underestimated the importance and significance of this religious duty, instead focusing on the allowances and exemptions provided in the Quranic verses. Through a semantic analysis of the language and structure of Q 2:183-5, the paper contends that the Quran emphasizes fasting as a crucial act of worship that should not be taken lightly. The conditional sentence structure in the verses is interpreted as a rhetorical device to highlight the benefits of fasting, rather than merely providing relief or exceptions. Furthermore, the paper argues that the Quranic mandate for fasting was not novel, as it built upon pre-existing fasting traditions among earlier faith communities like Judaism, Christianity, and even ancient Greek and Buddhist practices. This suggests that the first recipients of the Quran would have understood fasting as a serious religious obligation. In conclusion, the research challenges the common scholarly view that the Quran provides extensive leniency regarding the Ramadan fast. Instead, it posits that the Quranic approach emphasizes the importance and wisdom behind this act of devotion, which Muslims should not underestimate or treat too lightly.